PENGARUH PENDIDIKAN DAN KEMUDAHAN TRANSAKSI TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI BANGUNAN (KECAMATAN JATIASIH) - Ria Granida; Karsam (The Asia Pacific Journal Of Management Studies, 2025)
This study aims to determine the influence of education and transaction convenience on taxpayer compliance in paying Land and Building Tax (PBB) in Jatiasih District. The background of this research is based on the declining realization of PBB revenue from 2019 to 2021, indicating a decrease in taxpayer compliance. A quantitative approach was used with data collected through questionnaires distributed to 100 respondents who are taxpayers in the area. The data were analyzed using multiple linear regression with the assistance of SPSS. The results show that both education and transaction convenience have a partial and simultaneous influence on taxpayer compliance. The higher the level of education and the easier the transaction process, the higher the taxpayer compliance. This study is expected to provide input to local governments in improving taxpayer compliance through enhanced tax education and simplified payment systems